Simulation as a toolkit—understanding the perils of blood transfusion in a complex health care environment. Issue 1 (January 2016) - Campbell, Douglas; Poost-Foroosh, Laya; Pavenski, Katerina; Contreras, Maya; Alam, Fahad; Lee, Jason; Houston, Patricia
Abstract Background Administration of blood is a complex process requiring vigilance and effective teamwork. Despite strict policies and training on blood administration, errors still occur and can lead to mistransfusion with adverse patient outcomes. We used an in situ simulated scenario within an operating room (OR) to identify weaknesses in the current process and hazards that could contribute to mistransfusion. Methods A process checklist of critical steps of safe transfusion was developed based on a large academic centre's internal hospital policy and practice. Ten standardized operating room scenarios were conducted involving management of postoperative bleeding. Scenarios lasted 20 min or until blood transfusion was started. Debriefing followed immediately. Video recordings were reviewed, scored, and evaluated for team performance. Latent safety threats were identified. Focus groups further helped to identify rationale for decisions made. Participants completed questionnaires to evaluate the exercise. Results Forty-three experienced OR professionals participated. Of the 19 steps identified as essential for the safe administration of blood components, the median number of steps correctly completed per team was 11. The largest number of errors occurred when different team members interacted and during the immediate pre-transfusion check. We report that this type of learning immediately increased participants' self-reported ability to perform in a team (90%) and to improve clinical care (88%). Conclusions In situ simulation is valuable in identifying common susceptibilities in blood administration error in a complex healthcare organization. Administrators and clinicians may wish to use simulation as an opportunity for system improvement in the delivery of quality care.